Developing an Eclipse editor for MARC records using Xtext. (13th July 2012) - Surla, Bojana Dimić; Sicilia, Miguel‐Angel
SUMMARY In this paper, we present the idea of developing an editor for MAchine‐Readable Cataloguing records that is part of a library management system. The idea was realized and implemented as a part of the library management system BISIS. The objective was to generate an Eclipse plug‐in of the editor in an Xtext environment by specifying the Xtext grammar and generating an Eclipse Modelling Framework model of the MAchine‐Readable Cataloguing record. The next step was to specify additional features of the editor in the Xtext environment such as content assist and constraints on the record used for checking the correctness of the input. The implementation of additional functionalities of the editor was carried out in the Eclipse plug‐in development environment, and user interface components were implemented by using Standard Widget Toolkit and JFace libraries. A special emphasis is placed on the Eclipse extension model that relies on the Open Services Gateway initiative standard and enables efficient implementation of the systems with a component‐based, service‐oriented architecture. We took advantage of that model and created an extensible and adoptable application that can be used by any database management system and can be integrated in other library management systems. Finally, we discuss a possible way of extracting applications from Eclipse by using Rich Client Platform technology. Copyright © 2012 John Wiley & Sons, Ltd.